Studi Kepustakaan Analisis Bendungan Lere di Pulau Sabu, Kabupaten Sabu-Raijua, Propinsi NTT - Laurentia, Susilawati Cicilia; Purwantini, Purwantini; Sidiq, Alif Lombardoaji (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
Sabu Island, Sabu-Raijua Regency, is dry area, recorded having Lere Dam, which is no functioning, caused by a sinkhole in the inundation area, and the water disappears immediately becomes dry. The dam rehabilitation requires a desk-study for the potential agriculture and raw water produced. The study methodology includes: monitoring the existing dam; monitoring results analysis consisting of hydrological, geographical analysis and river basin simulation; recommendations for the axis location of the dam with its optimal and effective storage capacity. The results of the geographical analysis and simulation, show that the location of the main dam axis needs to be shifted upstream at the axis position from 10029'41.86"LS and 121056'37.39"BT to 10029'47.29"LS and 121056'41.87"BT. The rainwater catchment area obtained from this analysis is 415,5 ha. With a simulation of a 9,0 m embankment height, it will provide a reservoir storage volume of 1,100 MCM. As a conclusion, it can be written that this dam analysis desk-study is faster and more cost-effective in finding the optimal reservoir capacity and effective dam height. This study needs to be continued by conducting a field survey and detailed analysis.